Healthcare resource utilization and costs associated with patients prescribed afatinib or erlotinib as first-line therapy for EGFR mutation-positive NSCLC in the United States. (2nd January 2020) - Samuelsen, Carl; Lim, Jonathan; Golembesky, Amanda; Shrestha, Sulena; Wang, Li; Griebsch, Ingolf
Abstract: Aims: To assess healthcare resource utilization (HCRU) and costs in patients with non-small cell lung cancer treated with the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors afatinib or erlotinib as first-line treatment. Materials and methods: This retrospective analysis used data from three large administrative claims databases in the US: Truven MarketScan, IMS PharMetrics Plus, and Optum Clinformatics Data Mart. Patients with diagnosis codes of lung cancer treated with afatinib or erlotinib were included in the sample. Treatment cohorts were matched on baseline characteristics using propensity scores to account for potential selection bias. HCRU and healthcare costs were compared between the matched afatinib and erlotinib cohorts. Results: In total, 3, 152 patients met the study inclusion criteria; propensity score matching of the afatinib and erlotinib patients yielded 525 matched pairs with well-balanced baseline characteristics. The afatinib cohort had significantly fewer patients with ≥1 inpatient visits (40.4% vs 52.2%, p = 0.0001) and outpatient emergency room (ER) visits (45.7% vs 54.1%, p = 0.0066). Per patient per month (PPPM) visits were significantly different between afatinib compared to erlotinib for inpatient visits (0.1 vs 0.2, p = 0.0152), other outpatient visits PPPM (2.6 vs 3.0, p = 0.022) and outpatient office visits (2.0 vs 1.7, p = 0.0059). Although costs of outpatient office (1, 624 vs 1, 070; p = 0.0086) and pharmacy (6, 709 vs 5, 932; p < 0.0001) visits were higher for afatinib vs erlotinib, total costs did not differ significantly between cohorts (14, 972 vs 14, 412; p = 0.4415). Limitations: Retrospective claims data can be subject to coding errors or data omissions; patients were required to have continuous health plan enrolment; EGFR mutation status was not confirmed. Conclusions: Patients treated with afatinib as first-line monotherapy experienced fewer inpatient stays and ER visits compared with erlotinib. Total costs were not significantly different between the two treatment cohorts.